Pengaruh Variasi Gerakan Elektroda Pada Pengelasan Smaw Terhadap Uji Kekuatan Bending Baja ST 42 - Sultan Maulana Abdul Wahid; Kosjoko Kosjoko; Nely Ana Mufarida (Politeknik Negeri Ujung Pandang, 2023)
This study aims to determine the effect of straight groove, zigzag groove, and U pattern groove movement on the hardness and mechanical properties of the material in ST42 steel welding. The welding method used is shielded metal arc welding (SMAW) with a current strength of 100 Amperes. The test results show that the movement of the straight groove electrode gives the highest stress value in the bending test with an average of 1,168 MPa. The zig-zag groove electrode movement gave an average stress value of 1.127 Mpa, while the U pattern groove electrode movement gave an average stress value of 1.905 MPa. Microstructural testing showed that all electrode movements produced pearlite and ferrite phases, but straight groove electrode movements had more pearlite phases than the other movements. In addition, the zig-zag groove electrode flow and U pattern. This study provides a better understanding of the effect of electrode movement on the quality of welded joints, as well as providing important information in the development of industrial welding techniques.